Identification of a key smooth muscle cell subset driving ischemic cardiomyopathy progression through single-cell RNA sequencing - Wenyang Nie; Yong Wang; Yuanyuan Xiao; Zhiheng Lin; Jingwen Zhang; Zhijie Zhao; Zhen Wang (Scientific Reports)
Abstract Cardiomyopathy encompasses a range of diseases that severely affect the complex functions of the heart, involving structural and functional abnormalities, and is associated with high mortality. Recent studies have highlighted the critical role of ferroptosis in regulating oxidative stress and inflammation in cardiomyopathy. In this study, we established that the C6 S100A4+ SMCs subpopulation is critical by performing an integrated single-cell analysis of the known publicly available data GSE145154. We validated the role of S100A4 in SMCs through in vitro experiments, providing evidence for its potential as a therapeutic target. Furthermore, these cells interact with endothelial cells through the PTN-NCL pathway, influencing disease progression. Key transcription factors, including KLF2, FOS, FOSB, and JUNB, were identified. This key subpopulation, along with its associated signaling pathways, marker genes, stemness genes, and transcription factors, may offer new insights for preventing the onset and progression of cardiomyopathy, particularly ischemic cardiomyopathy.